A study of factors associated with the prevalence of coccidia infection in cattle and its spatial epidemiology in Busia, Bungoma and Siaya counties, Kenya - Makau, D.N. (University of Nairobi, 2014)
Coccidiosis is a protozoan infection that affects most domestic species: canine, feline, equine, porcine, bovine, ovine, lagomorphs and avian. The overall objective of this study was to determine the prevalence and spatial distribution of coccidia infection in cattle, and associated factors in different production systems in Busia, Bungoma and Siaya Counties Kenya. Specific objectives were to determine the prevalence and spatial distribution of coccidia infection in cattle as well as assess the factors associated with the infection in these Counties Kenya. The three Counties covered by the study were purposively selected for this study on prevalence of coccidia infection in cattle and associated factors in ‘unorganised’ production systems given that studies done in Kenya have concentrated on zero grazing and dairy production units. Also, being that this was part of a larger project in these areas (People Animals and their Zoonoses – PAZ); the three Counties were logistically favourable. The non-animal factors considered included: season, rainfall, housing, geographical location hygiene, nutrition, activity of the animals, and keeping of various species and veterinary attention. Animal related factors considered were: breed, age, gender, and physiological status (pregnant/lactating), body condition, and other infections. Households were then selected randomly using ArcMap 2.0 software to generate random points (and a back-up for each random point) within the study area. From the random point, the closest homestead within 300 m was selected for sampling. Spatial distribution of coccidian infection in these Counties was done using QGIS 2.0.1 software for mapping. Data on nutrition, seasons, housing, disease occurrence, veterinary attention, herd profile and use of the animals were obtained using questionnaire interviews. From the clinical examination, physiological status (lactating, pregnant), concurrent infections and presence of other endoparasites and ectoparasites were ruled in or out. Faecal samples (at least 5 gm) were collected directly from the rectum via digital extraction using lubricated gloves. Samples were analysed using McMaster and Kato Katz techniques. R Statistical software was used for univariate and multivariate logistic regression analysis of prevalence of coccidiosis in relation to various factors at p=0.1 and p=0.05 respectively. A total of 983 cattle were sampled from 416 households in all 3 Counties. Of this study population, 66% were female; about 273 cows had calved before in their life time at the time of study, 42.6% of these had calved within one year from the time of study. Prevalence of coccidia infection obtained using McMaster technique was 32.76% while Kato Katz technique indicted a prevalence of 8.75%. Given that these tests used different principles, the agreement was very weak with a calculated Kappa of 0.272 and a standard error of 0.029 (p=0.05). All significant variables at p=0.1 were then modelled in logistic regression model at p=0.05 with a backward elimination approach. These variables included: age, sex/gender, prophylactic treatment, regular vet visits, ploughing, treatment, lice and tick infestation. Only age was found to be statistically significant in explaining coccidia infection in cattle. Older animals were 0.71 times less likely to suffer from coccidiosis relative to younger animals. Clustering of bovine coccidia infection in space was evident with the resulting heat map indicating hotspots in South of Busia and North of Busia. Relationship between these clusters and geographical features revealed increased disease occurrence observed along river basins. This study showed that coccidia infection in cattle is prevalent in Busia, Bungoma and Siaya Counties at 32.76%. However coccidiosis in these three Counties presents in the subclinical form and thus no characteristic /overt clinical signs. Age was negatively associated with disease, a higher prevalence Oocysts per Gram count (OPGs) was observed in younger animals. Breed, level of activity, use of bulls for breeding, physiological status and concurrent infections were not significantly associated with infection at p=0.05. Good medical attention should be given to the calves and animals less than 30 months of age. Since the husbandry methods currently practised do not predispose cattle to coccidia infection, introduction of more intense farming methods may be accommodated only if high levels of hygiene are observed. Clustering of coccidia infection in cattle in Busia, Bungoma and Siaya Counties around wet lands and rivers indicated that common watering points pose a risk as disease foci and therefore farmers should be advised to water their animals from the homesteads or use clean water for their animals.